A novel design approach for micro-robotic appendages comprised of active and passive elements with disparate properties. (January 2022) - Milojević, Andrija; Shin, Minchul; Oldham, Kenn R
Recent innovations in microsystems materials and fabrication permit the creation of complex microactuation mechnisms with heterogeneous properties and behaviors. Meanwhile, emerging applications such as micro-robotics extend the environments in with microsystems may operate. This introduces substantial challenges for the design given the wide range of feasible devices. This paper describes a novel synthesis method based on structural topology optimization for the automated design of micro-robotic appendages realized by utilizing heterogeneous materials and embedded actuation. A typical mechanism designed by this approach, inspired by innovations in thin-film piezoelectric integration with other microstructures and materials, might include active smart actuators, elements formed from traditional semiconductor materials, and comparatively soft polymer flexures. We will introduce the framework for design optimization, and detailed procedure for problem definition, parameterization, and optimization. The focus of the synthesis is on realizing micro-robotic appendages that can achieve control of an end-effector in different directions (one and two). Original formulations of the optimization objective functions that lead to desired micro-robotic solutions are presented. Examples of different optimized designs are presented, with novel micro-robotic appendage solutions that can realize large in-plane displacement compared to prior devices, controllable actuation in largely-decoupled axes, and/or generation of unusual rotational displacement from initially planar geometries. Performance predicted by the design optimization algorithm is compared to simulated behavior through computational modeling. The presented synthesis method can be utilized by others to design micro-robotic solutions for different applications.